The Effect of RGEC on Share Prices (Case Study in the Banking Sector Listed on the IDX in 2020-2022) - Widya, Mesi; Kurniawan, Andy; Winarko, Sigit Puji (Universitas Nusantara PGRI Kediri, 2024)
Research aim: The purpose of this research is toconduct an analysis of the impact of the RGECcomponents which include Non-Performing Loans(NPL), Good Corporate Governance (GCG),Return onAssets (ROA), and Capital Adequacy Ratio (CAR) onshare prices of banking sector companies listed on theIndonesia Stock Exchange (BEI) during the 2020-2022period.Design/Methode/Approach:This research uses secondarydata obtained from the Financial Services Authority(OJK), the Indonesian Stock Exchange (BEI), and theofficial websites of the companies concerned.Research Finding: The results of the research show thatoverall RGEC (NPL, GCG, ROA, and CAR) has asignificant impact on banking company share prices. Inparticular, the NPL variable has no significant impact,while GCG and ROA have a significant positiveinfluence on stock prices. On the other hand, the CARvariable does not show a significant impact on stockprices. These findings can provide insight tostakeholders, especially investors, regulators andbanking company management, to better understand thefactors that influence share prices. This information canbe used as a basis for making more appropriatedecisions in managing investments and carrying outcorporate governance